Boganmeldelser - Per Ole Träskman; Britta Kyvsgaard; Preben Hertoft; Lena Hellblom Sjögren; Beth Grothe Nielsen; Vagn Greve; Peer Lorenzen; Lars Bo Langsted; Gorm Toftegaard Nielsen (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews